Biostimulatory effects of simvastatin on MDPC-23 odontoblast-like cells - Maria Luísa de Alencar e Silva Leite; Diana Gabriela Soares; Fernanda Gonçalves Basso; Josimeri Hebling; Carlos Alberto de Souza Costa (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The aim of this study was to evaluate the bioactivity and cytocompatibility of simvastatin (SV) applied to MDPC-23 odontoblast-like cells. For this purpose, MDPC-23 cells were seeded in 96-well plates and submitted to treatments with 0.01 or 0.1 μM of SV for 24 h, 72 h or continuously throughout the experimental protocol. The negative control group (NC) was maintained in DMEM. Cell viability (MTT), ALP activity (thymolphthalein monophosphate), and mineralized matrix deposition (alizarin red) were analyzed at several time points. The data were submitted to ANOVA and Tukey's test (α = 0.05). Although cell viability was observed in the groups treated with SV, these groups did not differ from the NC up to 7 days. There was a reduction in cell viability for the groups treated with 0.1 μM of SV for 72 h, and submitted to continuous mode after 14 days. A significant increase in ALP activity occurred in the group treated with 0.01 μM of SV for 24 h, compared with the NC; however, only the group treated with 0.1 μM of SV in continuous mode reduced the ALP activity, in comparison with the NC. After 14 days, only continuous treatment with 0.1 μM of SV did not differ from NC, whereas the other experimental groups showed increased mineralized matrix deposition. Thus, it was concluded that low concentrations of simvastatin were bioactive and cytocompatible when applied for short periods to cultured MDPC-23 odontoblast-like cells.